1989
DOI: 10.1002/ana.410250304
|View full text |Cite
|
Sign up to set email alerts
|

Amaurosis fugax associated with antiphospholipid antibodies

Abstract: In more than 50% of amaurosis fugax patients under 45 years of age no cause for the episodes of visual loss is identifiable. We have encountered 6 young adults (4 women and 2 men) with episodes of amaurosis fugax associated with elevated levels of antiphospholipid antibodies. Splinter hemorrhages of the nail beds were present in most patients. Treatment with antiplatelet medications and anticoagulants appeared to reduce the frequency of episodes and might prevent central retinal artery occlusions or stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(22 citation statements)
references
References 31 publications
1
21
0
Order By: Relevance
“…This relatively high percentage is not different from the 45.3% of cerebral infarcts of unknown cause observed in the Stroke Data Bank project [13], and it compares favorably with the findings of another study of retinal arterial occlusive disease [7]. Because detailed hematological evaluations were not obtained systematically in this study, it is possible that some patients in this subgroup suffered from hypercoagulable states [14, 15, 16]. Furthermore, transesophageal echocardiography was obtained in only 18.2% patients, so that some cardiac or aortic arch lesions may have been missed.…”
Section: Discussionmentioning
confidence: 68%
“…This relatively high percentage is not different from the 45.3% of cerebral infarcts of unknown cause observed in the Stroke Data Bank project [13], and it compares favorably with the findings of another study of retinal arterial occlusive disease [7]. Because detailed hematological evaluations were not obtained systematically in this study, it is possible that some patients in this subgroup suffered from hypercoagulable states [14, 15, 16]. Furthermore, transesophageal echocardiography was obtained in only 18.2% patients, so that some cardiac or aortic arch lesions may have been missed.…”
Section: Discussionmentioning
confidence: 68%
“…Likewise, several studies have reported the existence of a link between aPL and seizures in patients with SLE or in patients with the primary syndrome (11,12). Ocular disturbances (amaurosis fugax [2,13] and optic atrophy [2]), multiinfarct dementia, dementia of nonischemic origin (6,14,15), and chorea (16) have also been reported in patients with primary APS. Controversial reports exist regarding a similar association with nonspecific and migraine headaches (17,18), transverse myelitis (3,19), and Guillain-Barre syndrome (20).…”
Section: Introductionmentioning
confidence: 97%
“…Occasionally, the visual disturbance resembles the temporary loss of contrast vision typical of type II or the photopsias and scintillations of vasospastic type III. In several studies and in our own experience, no cause has been found to explain recurrent TMB type IV in young adults, apart from observations by Digre et al, 12 which document the association of TMB type IV in patients with anticardiolipin antibodies.…”
Section: Transient Monocular Blindness Type IVmentioning
confidence: 50%